Reference: its Patterns and Connotations in the Holy Verses of the Hypocrites - Fadhil Abbas , Lect .Dr. Udai (Basra studies journal, 2025)
Hypocrisy considered as one of the most dangerous social phenomena that the Holy Qur’an addressed with a precise rhetorical style. Due to the importance of this phenomenon and its danger to society, there was great emphasis on the verses that discussed the traits and actions of the hypocrites. Studies analyzed these verses and they varied, including textual studies that used reference (al-iḥālah) as a linguistic tool that connects texts to one another, which helps in understanding the intended meanings. This study aims to analyze reference in the verses of hypocrisy in the Holy Qur’an from a textual linguistic perspective, in order to uncover the methods of connection between sentences and verses, and the extent of their effect in conveying the meaning.